Applied Agrometeorology - Stigter, Kees (Springer, 2012)
The contents of this book are meant to assist applied agricultural scientists in learning from case studies and other background material how to apply agrometeorology better to solve problems in the livelihood of farmers and other agricultural producers. It also wants to create a renaissance in the teaching (that is education/training/extension) of applied agrometeorology at all levels, closer to the livelihood of farmers and other agricultural producers